2022
DOI: 10.1021/acsenergylett.2c02053
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Theory for H2 Evolution on Mo-Based Electrocatalysts

Abstract: Mo-based catalysts constitute a significant portion of active non-noble H 2 evolution reaction (HER) catalysts, but the role of Mo in conferring this activity remains debated. In this study, we utilize electrochemical, physical, functional, and computational approaches on a range of Mobased catalysts to derive a unified explanation for Mo HER catalyst function. Across all catalysts studied, the formation of Mo 3+ at cathodic potentials close to the thermodynamic HER onset drives activity, and activity between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…Bau found that the activity of Mo-based catalysts depends on the degree of reduction from Mo 4+ to Mo 3+ . 165 These results all provided guidance for the design and synthesis of HS catalysts at the atomic level.…”
Section: Catalysismentioning
confidence: 78%
“…Bau found that the activity of Mo-based catalysts depends on the degree of reduction from Mo 4+ to Mo 3+ . 165 These results all provided guidance for the design and synthesis of HS catalysts at the atomic level.…”
Section: Catalysismentioning
confidence: 78%
“…Thus, it should be reasonable to conclude that the newly generated signal should be ascribed to unpaired electrons from the Mo species of CZS, demonstrating that the decorated Mo species can trap unpaired electrons from the CZS. This tentative conclusion has been reconfirmed by increasing the Mo loading contents, in which the intensity of the signal has been further enhanced, and more radical pairs have been detected [32, 33] …”
Section: Figurementioning
confidence: 80%
“…This tentative conclusion has been reconfirmed by increasing the Mo loading contents, in which the intensity of the signal has been further enhanced, and more radical pairs have been detected. [32,33] Photocatalytic H 2 evolution efficiencies have been assessed in a closed circulation system under visible light (λ > 420 nm) irradiation. Lactic acid (20 vol %) has been applied as the sacrificial agent to consume the generated hole in the photoexcitation process.…”
mentioning
confidence: 99%
“…On the other hand, we have reported that, on electrochemically prepared NiMoO x , a Mo oxo species (most likely Mo 3+ that forms during the HER) supported on metallic Ni or NiMo alloy was responsible for the high HER activity as the site for hydride formation . This catalytic role of the Mo oxo species was also reported on other Mo-based electrocatalysts. , Because these mechanistic studies suggested the crucial role of partner atoms in activating the Mo oxo species, , it is worthwhile to design catalysts with Mo and other optimum elements for highly efficient HER.…”
Section: Introductionmentioning
confidence: 77%